The Effect of Raloxifene and Fluoxetine Treatment onOxidant-Antioxidant Status in Breast Cancer Bearing Rats - İlhan, Necip; Tatar, Oguzhan; Susam, Solmaz; İlhan, Nevin (My University, 2021)
Objective: 7,12-Dimethylbenz[a]anthracene (DMBA)-induced tumors in mammary tissue closelymimic human breast cancer in morphology and the expression of biochemical and molecularmarkers. Although significant advances have been seen in the treatment of breast cancer, there isstill a great need for alternative approaches. The current experiment was designed to investigatethe therapeutic effect of Raloxifene (RAL) and Fluoxetine (FLX) by assessing oxidant andantioxidant parameters in DMBA-induced breast carcinogenesis in rats.Materials and Methods: Thirty-two female Wistar rats were divided into 4 groups. Group I wastreated only DMBA. After tumor induction, cancer bearing rats were orally treated with RAL (GroupII), with FLX (Group III), and finally with RAL+FLX (Group IV), respectively. Tumors were induced inthe whole groups using DMBA dissolved in olive oil (80 mg/kg body weight). The tumor markercancer antigen (CA) 15-3 and selected oxidative and antioxidative parameters were analyzed inwhole experimental groups by using appropriate methods. Results: The oral treatment of the therapeutic agents alone or in combination provided asignificant decrease in CA 15-3 levels in all therapeutic groups compared to DMBA group. Whenthe level of malondialdehyde was measured, it was noticed a decrease in all treatment groupscompared to the DMBA group. Additionally, the activities of enzymatic antioxidants were renovatedto better after supplementation with the therapeutic agents, suggesting that this agents exhibitinganticancer effect.Conclusion: It was proposed that the combination of RAL and FLX was more effective than eachof RAL or FLX alone on restoration devastating effects of breast cancer.
Keywords: Endokrinoloji ve Metabolizma; Patoloji; Onkoloji; Biyokimya ve Moleküler Biyoloji